Legal support for information security of minors in the Eurasian Economic Union - Valiushko-Orsa, Natalia V. (Journal of the Belarusian State University. Law, 2025)
The article examines issues related to legal support for the information security of minors in the Eurasian Economic Union. Recommendations are made to improve the legal regulation of public relations in the field of information security of minors in the Eurasian Economic Union. It is proposed to develop and adopt at the level of the Eurasian Economic Union a concept of information security of minors. It is concluded that it is necessary to coordinate the efforts of the family, society and the state in protecting minors from destructive and illegal information, since only through joint efforts it is possible to get positive results in this very important and difficult matter.
Keywords: information security; minors; Eurasian Economic Union; legal protection; information